Antipsychotic use and unexpected death: A hospital-based case-control study - Mace,S; Dzahini,O; Cornelius,V; Anthony,D; Stewart,R; Taylor,D (Acta Psychiatrica Scandinavica, 2015)
Objective: To examine the risk of unexpected death in patients prescribed an antipsychotic. Unexpected death was defined as death occurring within 7 days of the onset of acute symptoms. Method: A case-control study conducted on events occurring between July 2009 and January 2011 in a UK mental health trust providing in-patient and out-patient services. Results: The study included 100 cases (deaths) and 436 unmatched controls. Current users of antipsychotics had a lower risk of unexpected death than non-users - adjusted odds ratio (OR) 0.48 (95% CI 0.24-0.94, P = 0.033). A significant reduction in risk was seen for second-generation [adjusted OR 0.42 (95% CI 0.21-0.86, P = 0.018)], but not first-generation agents [adjusted OR 0.83 (95% CI 0.31-2.20, P = 0.706)]. Treatment with antipsychotics for any duration was associated with reduced risk. Dose and route of administration did not affect risk. In a planned secondary analysis not adjusting for cardiovascular disease, prescription of an antipsychotic was not associated with increased risk of unexpected death [adjusted OR 0.56 (95% CI 0.28-1.08, P = 0.084)]. Conclusion: Our findings do not support an association between current antipsychotic use and increased risk of unexpected death.